Computed Tomography Predictors of Mortality or Disease Progression in Systemic Sclerosis–Interstitial Lung Disease: A Systematic Review - Landini, Nicholas; Orlandi, Martina; Bruni, Cosimo; Carlesi, Edoardo; Nardi, Cosimo; Calistri, Linda; Morana, Giovanni; Tomassetti, Sara; Colagrande, Stefano; Matucci-Cerinic, Marco (Frontiers in Medicine, 2022)
OBJECTIVE Although interstitial lung disease (ILD) is a major cause of morbidity and mortality in systemic sclerosis (SSc), its prognostication remains challenging. Given that computed tomography (CT) represents the gold standard imaging technique in ILD assessment, a systematic review on chest CT findings as predictors of mortality or ILD progression in SSc-ILD was performed. MATERIALS AND METHODS Three databases (Medline, Embase, Web of Science) were searched to identify all studies analyzing CT mortality or ILD progression predictors in SSc-ILD, from inception to December 2020. ILD progression was defined by worsening of forced vital capacity and/or CT ILD findings. Manuscripts not written in English, with not available full-text, not focusing on SSc-ILD or with SSc-ILD not extrapolated, otherwise including overlap syndromes, pediatric patients, < 10 cases or predictors other than CT features were excluded. RESULTS Out of 3513 citations, 15 full-texts (2332 SSc-ILD patients) met the inclusion criteria. ILD extent and extensive ILD, ILD densitometric analysis parameters, fibrotic extent and reticulation extent resulted as independent mortality predictors. Extensive ILD is also an independent predictor of death, need for supplemental oxygen or lung transplantation. Honeycombing extent is an independent risk factor for respiratory mortality. Independent predictors of ILD progression were not identified. CONCLUSIONS ILD extent and extensive ILD independently predict mortality in SSc-ILD on CT, as well as ILD densitometric analysis, fibrotic extent and reticulation extent. Extensive ILD is also a predictor of death, need for supplemental oxygen or lung transplantation. Honeycombing extent predicts respiratory mortality. CT predictors of ILD progression need to be further investigated.